Gestión alimenticia en un geriátrico - Guerrero Castillo, John Martin (2022)
The present work "Nutritional management in a geriatric" is a bibliographic review with the purpose of compiling, analyzing and addressing current scientific studies that provide accurate information about adequate nutrition in older adults, which covers the energy requirements, structural and regulators at this stage of their lives that guarantee this age group an optimal nutritional status; which will allow them to recover, prevent and/or prolong the appearance of signs or symptoms of diseases typical of the aging stage, maintaining an independent life that allows them to actively integrate into society and thus enjoy a better quality of life.